Community Knowledge about Antibiotics and the Role of Inter Professionals in Providing Health Education - Nurhidayah, Rika Endah; Sitanggang, Della Safitri; Ally Abdullah Ally (Caring: Indonesian Journal of Nursing Science, 2025)
Antibiotics are drugs to prevent or kill infections caused by bacteria. Antibiotics are not drugs that are freely available for consumption, therefore they should not be used carelessly. The use of antibiotics that is not in accordance with the rules can cause resistance to antibiotics. This study aims to identify the knowledge of the community in Kampung Mudik Village, Barus District and the role of health workers to prevent the effects of resistance to antibiotics. Methods: This study focused on the community in Kampung Mudik Village, Barus District. This study is a descriptive study. The sampling technique used a probabilistic technique with a margin of error of 5%. The number of respondents was 146 community. The result of study indicate that the level of community knowledge about antibiotics varies: most community (58.2%) have high knowledge, (28.8%) have sufficient knowledge, and (13%) have low knowledge. All community (100%) have used antibiotics, but the majority of community (79.5%) do not know the side effects of using antibiotics that are consumed carelessly. This study found that most community already have good knowledge about the use of antibiotics, but many community still do not know the side effects if they take antibiotics not according to instructions. Therefore, it is suggested that the community needs to be given proper education through inter-professional collaboration to avoid the effects of antibiotic resistance.